Carbon/NiO Compositional Fibers - Z.A. Mansurov; G.T. Smagulova; A.A. Imash; A.T. Taurbekov; B. Elouadi; B.B. Kaidar (Eurasian Chemico-Technological Journal, 2022)
This article presents the results of the synthesis of carbon-NiO composite fibers. Fibers doped with NiO particles are of practical interest for applications in sensors, energy storage systems, photocatalysts, etc. Four-component initial fibers based on polyacrylonitrile (PAN), activated carbon (AC), coal tar pitch (CTP), and NiO particles were obtained. CTP was obtained by thermal treatment of coal tar, AC by carbonization of apricot kernels, NiO by solution combustion synthesis. PAN, CTP, and AC are a source of carbon, but each of them plays a specific role. PAN is the basis of carbon fibers and a fiber-forming material, CTP is a technogenic waste added to replace polymer particles, AC is an additive that could increase the carbon content and the porosity of the final fibers. The fibers were obtained using the electrospinning method, which makes it possible to use complex suspensions and obtain fibers of various diameters. PAN:CTP:AC:NiO fibers were obtained. Next, the processes of stabilization and carbonization of the fibers were carried out. The fibers at each stage were examined by scanning electron microscopy and EDAX. The result of the synthesis was carbon/NiO fibers with a diameter of 100‒300 nm. The resulting fibers are promising for practical applications due to the one-dimensional structure of the fibers and better adhesion between the fiber and NiO particles.